APPLICATION OF EXTREME VALUE OF CHOQUE INTEGRAL IN DECIDING IN THE ECONOMIC THEORY OF THE ACTIVE CONNECT - O. V. Lavrichenko (Системный анализ и прикладная информатика)
Author is considered the basics of the economic theory of the active connect as well as the necessit y of reducing the action of anthropogenic factors on the effectiveness of additive models and decision-making algorithms is provided. The study analyzed the necessit y economic valuation of theanthropogenic successions within the concept of a balanced distribution of the industrial enterprises innovative resources. In article is considered that the existing approaches to the problem of optimizing Choque integral and its application in decision-making to address the disparit y in the distribution of innovative resources bet ween objects of innovation